Cold sprayed Cu–Ni–Fe anode for Al production. (January 2015) - Goupil, G.; Jucken, S.; Poirier, D.; Legoux, J.G.; Irissou, E.; Davis, B.; Guay, D.; Roué, L.
Highlights: Cu–Ni–Fe alloy was produced at large scale by ball milling. The Cu–Ni–Fe powder was deposited by cold spray to produce thick and adherent coating. Its nanocrystalline and monophased structure was retained during the deposition. It was evaluated as inert anode for Al electrolysis in low-temperature electrolyte. Aluminum with a purity of 99.3% was produced. Abstract: Inert anodes for Al electrolysis were produced by cold spray deposition of mechanical alloyed 65Cu20Ni15Fe powder. No structural change of the 65Cu20Ni15Fe alloy was observed during the cold spray processing apart from a small crystallite size increase. The electrochemical characterization was performed at 700 °C in a potassium cryolite-based electrolyte. A progressive increase of the cell voltage was observed during the 50 h of electrolysis. This is thought to reflect a decrease of the electrical conductivity of the anode attributed to the accumulation of electrolyte at the oxide/alloy interface and to the formation of insulating FeF2 precipitates in the bulk alloy.